Black humor and its allies in the work of Piedad Bonnett - González Valderrama, Jonnathan Leonardo (Rastros Rostros, 2017)
Purpose: To show the reader that humour is a critical tool if presented with scathing precision when using a diverse taxonomy in regards to it. This is how sarcasm, black humor, caricature, and irony become a source of intellectual approach to nonconformity, but also to the beauty of the characters and the poetic voices of Bonnett to face the fictional world, that is always a small mirror of a part of Colombian society.Methodology: This work is qualitative and tries to make a contrast between the passages of the novels and a selection of poems with the theory and criticism of the authors who have already “traveled” through the pages of the writer. This article is the result of a research work for the Master of Hispanic and Hispanic American Studies (research career), at the University of the Sorbonne Nouvelle Paris iii (France), during the period 2014-2015.Conclusions: Piedad Bonnett’s humour has a double side: as a philosophical position against what the characters or poetic voices criticize (theirs or others) or as a reward and commemoration.
Keywords: literature; education; humour; Bonnett; poetry; novel